2009
DOI: 10.1159/000189712
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of AP-1 Interference Induced by TAC-101 to Tumor Growth Suppression in a Hepatocellular Carcinoma Model

Abstract: TAC-101, 4-[3,5-bis(trimethylsilyl)benzamido] benzoic acid, is a synthetic ligand for retinoic acid receptor (RAR)-α. Here, we demonstrate the contribution of TAC-101-induced AP-1 interference to stabilization of tumor growth. TAC-101 induced transcriptional activation of RAR, resulting in marked elevation of RARβ, a representative retinoid response marker, and it also significantly repressed the transcriptional activity of AP-1 in JHH-7 cells. In contrast to JHH-7, JHH-6 is another RARα-expressing human hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A previous study has reported that the activity of AP-1 binding was increased by approximately 2.9-fold in the liver tumor compared with the nearby noncancerous tissue (Liu et al, 2002). In addition, it has been also suggested that AP-1 interferes with the suppression of tumor growth in HCC via the retinoid signals induced by 4-[3, 5-bis (trimethylsilyl) benzamido] benzoic acid (TAC-101) (Eshima et al, 2009). Therefore, FOS, as a constituent of the transcription factor AP-1, might affect the signal transduction pathway of cell proliferation and apoptosis by pathological stimuli in human HCC (Guo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that the activity of AP-1 binding was increased by approximately 2.9-fold in the liver tumor compared with the nearby noncancerous tissue (Liu et al, 2002). In addition, it has been also suggested that AP-1 interferes with the suppression of tumor growth in HCC via the retinoid signals induced by 4-[3, 5-bis (trimethylsilyl) benzamido] benzoic acid (TAC-101) (Eshima et al, 2009). Therefore, FOS, as a constituent of the transcription factor AP-1, might affect the signal transduction pathway of cell proliferation and apoptosis by pathological stimuli in human HCC (Guo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%